Revolutionizing TOD Planning in a Developing Country: An Objective-Weighted Framework for Measuring Nodal TOD Index - Md. Anwar Uddin; Tahsin Tamanna; Saima Adiba; Sadib Bin Kabir (Journal of Advanced Transportation)
Transit-oriented development (TOD) is a planning strategy that combines land use and transportation planning to promote economic, environmental, and social sustainability. While developed cities have embraced TOD, developing cities need to adopt it faster. This has resulted in a need for robust TOD measurement frameworks for developing countries. Furthermore, existing frameworks often use subjective weightage for different TOD indicators, which can lead to human biases. To address these issues, the authors aimed to develop a more robust and objective framework for measuring TOD in developing cities, particularly Dhaka, Bangladesh. The authors used density, diversity, destination accessibility, and design criteria to select eight indicators for measuring TOD. However, a buffer radius of 800 meters was taken for each of the 17 stations to calculate TOD. An objective-weighted spatial multi-criteria analysis (OSMCA) was used to evaluate the framework. The model’s robustness was assessed by analyzing the sensitivity of eight TOD scenarios and identifying hotspot clusters using statistical methods. Additionally, the authors ranked the stations based on the highest TOD score and compared TOD with developed and developing cities to gain planning insights. They proposed three different TOD planning methodologies for nodes that emphasize the importance of design, destination access, and density for (re)development, zoning, and affordable housing policies in Dhaka’s regions. Finally, the study discussed limitations and future research priorities.